2005
DOI: 10.1002/dvdy.20494
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for β‐ and γ‐crystallins in the vascular remodeling of the eye

Abstract: We demonstrate that expression of ␤-and ␥-crystallins is associated with intraocular vessels during normal vascular development of the eye and also in the Nuc1 rat, a mutant in which the hyaloid vascular system fails to regress normally. Real-Time RT PCR, Western blot and metabolic labeling studies indicate an increased expression of ␤-and ␥-crystallins in Nuc1 retina. The increased expression of crystallins was localized to the astrocytes surrounding the intraocular vessels. A similar pattern of crystallin ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 59 publications
2
47
0
Order By: Relevance
“…Remodeling is critical to retinal development and maturation, by generating the different cell types in proper ratios and positions, which then migrate to correct layers before finally forming synaptic connections. Third, we have recently shown persistence of the fetal vasculature in this model (Zhang et al, 2005). Regression of the fetal vasculature is an essential element of eye development, apoptosis is vital to this process (Lobov et al, 2005).…”
Section: Maumenee Personal Communication)mentioning
confidence: 75%
See 3 more Smart Citations
“…Remodeling is critical to retinal development and maturation, by generating the different cell types in proper ratios and positions, which then migrate to correct layers before finally forming synaptic connections. Third, we have recently shown persistence of the fetal vasculature in this model (Zhang et al, 2005). Regression of the fetal vasculature is an essential element of eye development, apoptosis is vital to this process (Lobov et al, 2005).…”
Section: Maumenee Personal Communication)mentioning
confidence: 75%
“…Our previous study demonstrated expression of βA3/A1-crystallin mRNA in the retina (Zhang et al, 2005). To determine its cellular localization within the retina, laser-capture microdissection was employed.…”
Section: Maumenee Personal Communication)mentioning
confidence: 99%
See 2 more Smart Citations
“…␣-Crystallins belong to the small heat shock protein family and prevent aberrant protein interactions and/or degradation and regulate apoptosis (13)(14)(15)(16). The functions of the ␥-and ␤-crystallins are less clear, although like the ␣ family they are involved in chaperone activity, apoptosis regulation, and vascular remodeling in the retina (17,18).…”
mentioning
confidence: 99%